Utilization Of Geospatial Intelligence (Geoint) In The Intelligence Cycle To Support The Role Of State Intelligence In Indonesia - Djati, Wisnu Hastungkoro; Gunawan, Diah Setyorini (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
The development of information technology has changed the paradigm of access to intelligence resources globally, including in the field of Geospatial intelligence (Geoint). Geoint integrates Imaginary intelligence (Imint) and Geospatial data (Geoinfo) in the context of strategic intelligence for comprehensive collection and analysis of geographic conditions and enemy activities. This paper highlights the utilization of Geoint in supporting the role of state intelligence in Indonesia in the intelligence cycle. The result of this paper shows the potential of Geoint to be utilized in supporting the role of intelligence organizations, especially in Indonesia, in dealing with dynamic threats that are evolving into new-style warfare. In the intelligence cycle, Geoint provides the necessary geospatial data and information and facilitates the process of planning, collecting, processing, and distributing information to support national security policy.